2022
DOI: 10.21468/scipostphys.12.5.150
|View full text |Cite
|
Sign up to set email alerts
|

Probing the particle spectrum of nature with evaporating black holes

Abstract: Photons radiated from an evaporating black hole in principle provide complete information on the particle spectrum of nature up to the Planck scale. If an evaporating black hole were to be observed, it would open a unique window onto models beyond the Standard Model of particle physics. To demonstrate this, we compute the limits that could be placed on the size of a dark sector. We find that observation of an evaporating black hole at a distance of 0.01 parsecs could probe dark sector models containing one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…In ref. [69] we demonstrated that if the HAWC observatory observed ∼ 200 photons from an exploding black hole it could probe dark sector models containing one or more copies of the SM particles with any mass scale up to 100 TeV.…”
Section: Introductionmentioning
confidence: 83%
“…In ref. [69] we demonstrated that if the HAWC observatory observed ∼ 200 photons from an exploding black hole it could probe dark sector models containing one or more copies of the SM particles with any mass scale up to 100 TeV.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, ref. [60] studied the potential implications of discovering such a low-mass PBH nearby: since such an object would be actively evaporating, the relationship between the object's mass and evaporation rate would enable a direct count of the number of dark-sector degrees of freedom. Our calculation suggests that if a population of such objects were maintained for a sufficiently long time, then there would be good prospects to find one close enough to be studied in this manner.…”
Section: Compact Object Capture In Different Systemsmentioning
confidence: 99%
“…Noteworthy, HR is a purely gravitational phenomenon. As such, BHs would radiate any dark sector particle in addition to the Standard Model (SM) spectrum, such as supersymmetric states [7], DM or dark radiation (DR), e.g. [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%